Assessment of Knowledge, Attitude and Practice of Community Pharmacists towards Adverse Drug Reactions Reporting in Pokhara - Chaudhary, Aswani; Pariyar, Sujan; Dahal, Bibek; Thapa, Shankar (Nepal Journal of Health Sciences, 2024)
Introduction: The pharmacovigilance activities were initiated since 2004 AD which promote Adverse Drug Reactions (ADRs) reporting in hospital-based set-up in Nepal. But the system lacks robust activities related to ADRs and its reporting on community-based pharmacy. The role of pharmacist is very essential in preventing harmful effects of medicine. Objective: The main objective of the research is to assess the knowledge, attitude and practice of community pharmacists towards ADR reporting and to correlates the KAP scores with the demographic distribution of the respondents. Methods: A cross-sectional study was carried out by using a self-administered structured questionnaire. During the study period 132 pharmacists working at community pharmacies in Pokhara were selected and they were interviewed. Results: Out of 132 pharmacies visited, with an overall response rate of 65.33%, only 87 pharmacists agreed to response. There were 56 males and 31 females. The pharmacists with post-graduation degree had a high KAP score (21.00) followed by PharmD (19.5), graduate pharmacists (19.35), and then assistant pharmacists (13.8). Conclusion: Majority of the pharmacist had relatively better attitude but good knowledge towards ADRs and pharmacovigilance. In spite of that the knowledge and attitude could not reflected on the practice of ADR reporting. The majority of respondents emphasize the reporting of ADR from ground level is essential, so that the outcome-based treatment can enhance the patient’s safety.